2013
DOI: 10.3899/jrheum.120680
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Catalytic Proteasome Subunits and Resistance Toward Proteasome Inhibition of B Lymphocytes from Patients with Primary Sjögren Syndrome

Abstract: In pSS, catalytic subunits of the proteasome are upregulated at the mRNA level, while dysregulation of subunit β1i is attributed to B lymphocytes. B cell resistance after proteasome inhibition differs from the classical concept of increased susceptibility toward inhibition in activated cells, supporting the novel notion that susceptibility depends on cellular intrinsic factors and on proteasome activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…As a result of duplication in Case4, the overexpression of TBP can occur, causing the failure of oocyte maturation. The 6q27 region also includes PSMB1 ( proteasome subunit , beta-type , 1 , MIM*602017), associated with Sjögren's syndrome ( Martinez-Gamboa et al , 2013 ), a chronic autoinflammatory disease, suggesting autoimmune reactions as the cause of this patient’s POF at the age of 24 years. SCARB1 ( scavenger receptor class b , member 1 at 12q43; MIM*601040), detected in Case 9, mediates cholesterol transfer to and from high-density lipoprotein (HDL).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of duplication in Case4, the overexpression of TBP can occur, causing the failure of oocyte maturation. The 6q27 region also includes PSMB1 ( proteasome subunit , beta-type , 1 , MIM*602017), associated with Sjögren's syndrome ( Martinez-Gamboa et al , 2013 ), a chronic autoinflammatory disease, suggesting autoimmune reactions as the cause of this patient’s POF at the age of 24 years. SCARB1 ( scavenger receptor class b , member 1 at 12q43; MIM*601040), detected in Case 9, mediates cholesterol transfer to and from high-density lipoprotein (HDL).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, PSMB5 (β5) subunits were often found upregulated upon BTZ exposure in BTZ-resistant cells to compensate for inhibitory effects on proteasome activity [ 51 ]. Interestingly, Martinez-Gamboa and colleagues [ 52 ] observed that intrinsic factors and aberrant proteasome activation established dysregulation of β1i proteasome subunit expression in B lymphocytes of SS patients, conferring diminished PI inhibition and resistance to apoptosis. PI exposure and resistance may also provoke alterations in the relative composition of constitutive and immunoproteasome subunits, the impact of which on immune functions is not clear [ 53 , 54 ].…”
Section: Mechanisms Of Proteasome Inhibitor Resistance and Implicatiomentioning
confidence: 99%
“…23 Interestingly, dysregulated expression levels of catalytic proteasome subunits have been detected in peripheral blood mononuclear cells (PBMCs) from patients with primary SS (pSS). 24 Moreover, the expression of LMP7 was significantly increased in the minor salivary glands of patients with SS. 25 Although previous studies have indicated the involvement of proteasome activation in SS development, it remains largely unknown whether inhibition of the proteasome possesses any therapeutic benefits for the treatment of SS.…”
Section: Introductionmentioning
confidence: 96%